1980
DOI: 10.1104/pp.65.6.1062
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydration State and Thiol-Disulfide Status in the Control of Thermal Stability and Protein Synthesis in Wheat Embryo

Abstract: Reduced (GSH), oxidized (GSSG), and protein-bound (PSSG) glutsthione were-determined in dry and hydrated wheat embryos. Dry embryos contained-about 0.6 tkmoles per gramdry weight each of GSSG and PSSG, and thege levels declned 5-to lO4fold within minutes after the onset of imbibition. GSH declined from about 8 to 2pmoles per gram over a peiod of 90 minutes. Similar changes occurred when embryos were hydrated by storage at 100% relative humidity. The decline in glutathione levels was not reversed-upon redrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 13 publications
3
19
1
Order By: Relevance
“…This result reveals the function and efficiency of the GR enzyme (Fig. This relationship is consistent with the changes in the GSH levels found in aged tomato (De Vos et al 1994) and sunflower seeds (De Paula et al 1996), with rapid reduction of GSSG upon imbibition of isolated wheat embryos (Fahey et al 1980) and in imbibing pea seeds (Kranner and Grill 1993), and with the changes detected in GR activity (Klapheck et al 1990, Cakmak et al 1993, Bailly et al 1996. Thus, activation of the GSSG-reducing system, together with the removal of MDA, generates a more reduced environment that promotes normal cell function.…”
supporting
confidence: 85%
“…This result reveals the function and efficiency of the GR enzyme (Fig. This relationship is consistent with the changes in the GSH levels found in aged tomato (De Vos et al 1994) and sunflower seeds (De Paula et al 1996), with rapid reduction of GSSG upon imbibition of isolated wheat embryos (Fahey et al 1980) and in imbibing pea seeds (Kranner and Grill 1993), and with the changes detected in GR activity (Klapheck et al 1990, Cakmak et al 1993, Bailly et al 1996. Thus, activation of the GSSG-reducing system, together with the removal of MDA, generates a more reduced environment that promotes normal cell function.…”
supporting
confidence: 85%
“…Higher amounts of GSH and GSSG in dry embryos compared to germinating seeds were also noted which prevents further germination process (Tommasi et al 2001). Fahey et al (1980) also suggested that presence of GSSG in dormant wheat embryos block protein synthesis. These reports strongly supports our results that higher amounts of GSH and GSSG in non-embryogenic callus may be due to protein synthesis blockage preventing further development leading to yellowish brown callus.…”
Section: Resultsmentioning
confidence: 95%
“…Mixed disulphide formation was also observed during desiccation of wheat grains, along with a decrease in the GSH/GSSG ratio and GR activity (Rhazi et al 2003). Rehydration of wheat embryos resulted in rapid reduction of PSSG within the first 10 mins of imbibition (Fahey et al 1980).…”
Section: S-glutathionylation In Stressed Plantsmentioning
confidence: 95%